Comparative Study of Nursing PhD Education System and Curriculum in Iran and Yale of USA - Moesen Adib-Hajbaghery; Shanaz Bolandian bafghi; Zohreh Nabizadeh gharghozar (Babol University of Medical Sciences, 2020)
Background: The knowledge and skills of nursing PhD graduates have a great impact on the nursing profession. Due to the impact of curriculum on roles and tasks, multiple studies are needed to identify the strengths and weaknesses of the curriculum. Therefore, in this study, we decided to compare nursing doctorate program in Iran with Yale University.  Methods: This is a descriptive comparative study, which is done by using Bereday's model in four stages of description, interpretation, juxtaposition and comparison in 2018. The data was obtained from the Ministry of Health and Medical Education and The Yale Nursing PhD program was obtained from "nursing.yale.edu". Findings There are significant differences between key elements such as philosophy, mission, curriculum content, and the role of Iranian Nursing PhD graduates with Yale. The philosophy of PhD in Nursing in Iran is to promote Islamic values with the aim of promoting health and providing a fair health service for Yale University. The mission of the Iranian Nursing PhD is to promote and enhance the skills of nurses and for Yale University is to provide better health for individuals.  Discussion and Conclusion: Most nursing PhD graduates in Iran are less likely to work in bed. This may be due to the inconsistency between the philosophy, mission and goals of the nursing PhD program. Considering the role and duties of the graduates of this course, it is advisable to reconsider the goals, mission and content of the nursing PhD curriculum.